2017
DOI: 10.1111/josh.12478
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Nutrition Education Combined With Fruit and Vegetable Taste Testing Improves Children's Dietary Intake

Abstract: The FFVSP and GWWFV with taste testing demonstrated a positive influence on FV intake in third grade children. Leveraging environmental approaches with interactive learning experiences create desired outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 27 publications
4
45
0
3
Order By: Relevance
“…Indiana FSDs and CHCs may benefit from utilizing (and/or continuing to utilize) the Land Grant University Extension system because Extension is already an institutionalized and active component of many communities and coalitions. For example, Extension Educators in North Dakota and Maryland spearheaded successful nutrition education interventions in schools. There are many opportunities for long‐term partnerships and consolidation of resources and skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indiana FSDs and CHCs may benefit from utilizing (and/or continuing to utilize) the Land Grant University Extension system because Extension is already an institutionalized and active component of many communities and coalitions. For example, Extension Educators in North Dakota and Maryland spearheaded successful nutrition education interventions in schools. There are many opportunities for long‐term partnerships and consolidation of resources and skills.…”
Section: Discussionmentioning
confidence: 99%
“…19 Additionally, school collaboration with the Land Grant University Extension system has promising implications for nutrition education of students and parents. 20,21 Our initial interviews with CHCs indicated that coalitions view school wellness as an opportunity to promote nutrition education, school gardens, local foods, and effective/safe utilization of foods wasted during school meals. Though FSDs and CHCs both address school wellness and nutrition, their perceived feasibility of school and community nutrition programs, as well as their priorities for accomplishing public health goals (ie, meeting federal policy requirements and/or expanding local community health promotion efforts) may vary.…”
Section: Whereasmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, schools can combine classroom instruction with hands‐on activities including taste‐tests, cafeteria lessons, or school gardens to allow students to integrate their knowledge and increase their exposure to positive messages about healthy eating. In a sample of third grade students, nutrition education combined with fruit and vegetable taste testing led to an increased consumption of fruits and vegetables than nutrition education alone . A school garden pilot program was also linked to increased consumption of fruits and vegetables in elementary‐aged children, as more than 90% of students enjoyed the gardening experience, particularly the responsibility it gave them …”
Section: Implications For School Healthmentioning
confidence: 99%
“…In a sample of third grade students, nutrition education combined with fruit and vegetable taste testing led to an increased consumption of fruits and vegetables than nutrition education alone. 39 A school garden pilot program was also linked to increased consumption of fruits and vegetables in elementary-aged children, as more than 90% of students enjoyed the gardening experience, particularly the responsibility it gave them. 40 Finally, schools can strive to market healthier options to students by making healthy options convenient and appealing.…”
Section: Implications For School Healthmentioning
confidence: 99%